2013
DOI: 10.1523/jneurosci.1631-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Spinal   and   Opioids Inhibit Both Thermal and Mechanical Pain in Rats

Abstract: The expression and contribution of (MOPR) and ␦ opioid receptors (DOPR) in polymodal nociceptors have been recently challenged. Indeed, MOPR and DOPR were shown to be expressed in distinct subpopulation of nociceptors where they inhibit pain induced by noxious heat and mechanical stimuli, respectively. In the present study, we used electrophysiological measurements to assess the effect of spinal MOPR and DOPR activation on heat-induced and mechanically induced diffuse noxious inhibitory controls (DNICs). We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 84 publications
0
31
0
3
Order By: Relevance
“…Finally, an insufficient population of DOPrs is present in substance P-containing neurons to produce a physiologic effect (Bardoni et al, 2014). Nevertheless, DOPr immunoreactivity was identified in substance P neurons within the myenteric plexus of the small intestine of DOPr-eGFP knock-in mice (Poole et al, 2011), demonstrating that DOPrs can be coexpressed with substance P. Moreover, DOPr activation also inhibits substance P release from primary afferents (Beaudry et al, 2011;Kouchek et al, 2013;Normandin et al, 2013). The dispute over whether DOPrs are present in substance P-containing neurons remains unresolved, because in situ hybridization and single-cell polymerase chain reaction studies report different results Wang et al, 2010).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%
“…Finally, an insufficient population of DOPrs is present in substance P-containing neurons to produce a physiologic effect (Bardoni et al, 2014). Nevertheless, DOPr immunoreactivity was identified in substance P neurons within the myenteric plexus of the small intestine of DOPr-eGFP knock-in mice (Poole et al, 2011), demonstrating that DOPrs can be coexpressed with substance P. Moreover, DOPr activation also inhibits substance P release from primary afferents (Beaudry et al, 2011;Kouchek et al, 2013;Normandin et al, 2013). The dispute over whether DOPrs are present in substance P-containing neurons remains unresolved, because in situ hybridization and single-cell polymerase chain reaction studies report different results Wang et al, 2010).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%
“…Recent studies have shown that both thermal and mechanical hyperalgesia are inhibited by either δ‐ or μ‐opioid receptor agonists through the activation of δ‐ or μ‐opioid receptors, respectively, in nociceptive afferents (Joseph and Levine, ; Gaveriaux‐Ruff et al ., ; He et al ., ; Kim et al ., ; Normandin et al ., ). These results are consistent with the coexistence of δ‐ and μ‐opioid receptors in peptidergic small DRG neurons, and support the notion that δ‐ and μ‐opioid receptors interact in the nociceptive sensory circuit.…”
Section: Role Of Opioid Receptor Interaction In Morphine Antinociceptmentioning
confidence: 97%
“…Early autoradiographic studies showed that many opioid receptors and the binding sites for μ‐ and δ‐opioid receptor agonists, are present in nociceptive afferent Aδ‐ and C‐fibres terminating in the superficial dorsal horn of the spinal cord (Fields et al ., ; Moskowitz and Goodman, ; Gouarderes et al ., ; Besse et al ., ; Mennicken et al ., ). Moreover, the release of the excitatory neurotransmitter glutamate, the neuropeptides substance P and CGRP from afferent C‐ and Aδ‐fibres could be inhibited by activating δ‐opioid receptors with several δ‐opioid receptor agonists (Ueda et al ., ; Zachariou and Goldstein, ; Beaudry et al ., ; Normandin et al ., ), suggesting the presynaptic localization of δ‐opioid receptors on nociceptive afferents. This notion was supported by the finding that δ‐opioid receptor mRNA is present in about 70% of DRG neurons, including both peptidergic [isolectin B4 (IB4)‐negative] and non‐peptidergic (IB4‐positive) subsets of small neurons and mechanoreceptive large neurons, while μ‐opioid receptors were expressed in the subsets of small DRG neurons and some large DRG neurons (Arvidsson et al ., ; Minami et al ., ; Wang and Wessendorf, ; Wang et al ., ; Gaveriaux‐Ruff et al ., ; He et al ., ).…”
Section: Co‐expression Of Opioid Receptors In Nociceptive Afferent Nementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, stimulation of both spinal and peripheral -, ␦-, and -opioid receptors has been shown to exert potent antinociceptive effects in a variety of pain models (15,23,24,26). Our laboratory has demonstrated recently that stimulation of -opioid and ␦-opioid receptors located on the peripheral endings of hindlimb muscle afferents attenuated the exaggerated exercise pressor reflex in rats with ligated femoral arteries (17, 37).…”
mentioning
confidence: 99%